Stator flux‐oriented vector control of dual stator induction generator with time optimised 11‐zone hybrid PWM for grid connected wind energy generation system. Issue 11 (24th October 2018) - Chatterjee, Shantanu; Chatterjee, Saibal
Abstract : This work presents a novel stator flux‐oriented vector control (SFOVC) of a dual stator induction generator (DSIG) used for a grid connected, variable speed wind energy generation system. The DSIG consists of two stator windings electrically separated by an angle of 30° with dissimilar pole numbers, which are in the ratio of 1:3. In conventional vector control, the rotor flux is oriented along the d ‐axis of the rotor winding. However, the rotor variables are not easily accessible. So, in the SFOVC, the total flux is made to be oriented along the d ‐axis of the stator winding. SFOVC is advantageous as compared to conventional vector control because the stator variables are easily accessible and do not require any special arrangement for the measurement of variables which increases the robustness of the system. Here, two separate converters are used for the two stator windings of the machine and the converter switching is being controlled by a novel space vector based 11‐zone hybrid pulse‐width modulation (PWM). This special PWM results in better harmonic performance, reduced torque pulsation and minimal switching loss. The overall simulation is being performed in MATLAB Simulink environment and the simulated results are also being validated experimentally.